PENGARUH ARUS KAS BEBAS, KEBIJAKAN PENDANAAN, PROFITABILITAS, COLLATERAL ASSETS TERHADAP KEBIJAKAN DIVIDEN - Suci, Rizky Indra Wulan; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
Dividend policy issues concern about the use of profits which has become the rights of shareholders profit sharingin the amount of dividend which will be paid depends on the policy of each company. Companies need to considervarious factors in the making of decisions regarding the distribution of dividends so that profits which aredistributed is in proportion they owned. This research is meant to examine the influence of free cash flow,financing policies, profitability, and collateral assets to the dividend policy. The samples are the consumer goodsindustry sector companies which are listed in Indonesia Stock Exchange (BEI) in 2011-2014 periods. The sampleselection techniques has been done by using purposive sampling method and based on the specified criteria, 16companies have been acquired as research samples. The data has been obtained from the Indonesia StockExchange and the examined financial statements which have been audited in 2011-2014. The data analysismethod has been done by using multiple linear regressions analysis. The result of statistics t test shows that thefree cash flow and financing policy has positive influence whereas collateral assets has negative influence ondividend policy. Profitability does not have any influence on the dividend policy.Keywords: Free Cash Flow, Financing Policies, Profitability, Collateral Assets, Dividend Policy